Make cities and human settlements inclusive, safe, resilient and sustainable - Kristie Daniel (UN Chronicle, 2015)
A vision for cities has never been more important than it is today. More than half of the world’s inhabitants live in cities and this migration trend is expected to continue. By 2050 more than two-thirds of the world will be urban dwellers. India alone is expected to double the number of city dwellers by adding 404 million new people to cities over the next 35 years.